DIGITAL APPLICATIONS IN PHYSICAL EDUCATION: EXPERIENCE, BENEFITS, AND IMPLEMENTATION CHALLENGES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article presents the attitudes of physical education teachers toward the use of digital applications, highlighting their advantages and challenges. The aim is to examine teachers' perspectives on the implementation of digital applications in physical education and identify their benefits and difficulties. The study employed literature analysis, surveys, and statistical processing of research results. It was found that 62,9% of teachers incorporate digital applications into their pedagogical practice, while 42,9% started using them during the strict lockdown period. Additionally, 37,1% primarily apply them in distance learning and occasionally in face-to-face lessons. Among various digital tools, teachers prefer interactive learning platforms (67,1%), fitness trackers (34,3%), and applications for monitoring pupils' health (30.0%). Regarding the impact, 31,4% of teachers recognize the positive influence of digital applications on pupils’ motivation, 52,9% believe they facilitate individualized learning, 41,4% consider them effective for health-related tasks, and 48,6% note their role in developing pupils’ physical qualities. However, the effectiveness of digital applications in achieving educational (31,5%) and educational-social (25,7%) objectives in physical education remains low. The study identifies key advantages, such as access to diverse educational materials (47,1%), individualized learning (32,9%), increased pupil motivation (20,0%), improved progress monitoring (17,1%), and enhanced communication with pupils and parents (15,7%). Challenges include difficulties in integrating applications into the learning process (71,4%), lack of time for preparation and implementation (62,9%), insufficient technical support (38,6%), lack of necessary equipment (37,1%), and low digital literacy among teachers (37,1%). The findings suggest that physical education teachers actively use digital applications, with fitness trackers and health-monitoring tools being the most popular. While teachers find them less effective for achieving educational and social objectives, they recognize their significant role in tracking pupils’ physical development and health status.